Menjaga Kualitas Obat Lewat Edukasi Beyond Use Date (BUD) di Puskesmas Sumbang II Banyumas - prabandari, rani; Ammanu Kurniadi; Andrea Arum Sekar; Anisa Rakhma Diantri; Armelia Allya Sandika; Bellina Faradhita Luxfi (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Introduction: Because drug abuse and other issues may arise from the increased use of pharmaceuticals without proper understanding, determining the Beyond Use Date (BUD) is of the utmost importance. Since women may serve as